تأثير تمرينات مقترحة بمصاحبة بعض وسائل العلاج الطبيعي في التخفيف من حدة الالم والقوة العضلية للرياضيين المصابين بالقطع التام للرباط الصليبي الامامي لمفصل الركبة (Journal of the College of Basic Education, 2024)
The research aims to prepare rehabilitation exercises using suggested and easy -to -implement exercises and use some of the various methods manufactured and proposed in improving the muscle strength of the knee joint for players with complete cuts of the front cruciferial ligament after surgical interference as well as the use of easy therapeutic methods, which are ultrasound and electrical therapy (GAL - FARADIC - Tens) and infrared, which is one of the natural means, so the researcher decided to search in all the aforementioned means to identify the extent of its impact on the rehabilitation of the front cruciate ligament and the return of the injured athlete to exercise his activity as short as possible. The researcher used the experimental curriculum in the style of (one group) with the two tribal and posttests to comprehend the nature of the problem. The sample was chosen in the intention of 3 (3) players with a complete cutting of the front cruciate ligament after the surgical interference based on a medical report from the specialist doctor. The main experience (qualifying curriculum) was conducted by (12) weeks and (3) days per week, and after obtaining data due to tests and measurements it was addressed according to the statistical bag (SPSS) to analyze the results and ensures statistical schedules that were discussed scientifically depending on the presentation, analysis and document To Arab and foreign sources, as well as previous studies. In light of the results reached by the researcher came out with the following conclusions: the curriculum prepared has a positive effect in improving the muscle strength of the knee joint after the surgical interference of the front cruciate ligament, and that the use of exercises and the proposed and manufactured physiotherapy means are very effective in improving muscle strength, also that the use of exercises and means The manufacturer did not leave any negative effects on the sample, but rather obtained positive effects and a rapid improvement in muscle strength. In light of these conclusions reached by the researcher, it recommends the necessity of using the proposed rehabilitation exercises for the curriculum because of the improvement in the rehabilitation of the fully cutting of the front cruciate ligament after the surgical overlap of members of the research sample.